2018
DOI: 10.48550/arxiv.1801.06046
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conditions for wave trains in spiking neural networks

Johanna Senk,
Karolína Korvasová,
Jannis Schuecker
et al.

Abstract: Spatiotemporal patterns such as traveling waves are frequently observed in recordings of neural activity. The mechanisms underlying the generation of such patterns are largely unknown. Previous studies have investigated the existence and uniqueness of different types of waves or bumps of activity using neural-field models, phenomenological coarse-grained descriptions of neural-network dynamics. But it remains unclear how these insights can be transferred to more biologically realistic networks of spiking neuro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 122 publications
(228 reference statements)
0
12
0
Order By: Relevance
“…The topographic pattern of connection is interrupted in the network edges, changing the activity in the network boundary [14,15]. A classic solution adopted to this problem is the torus connection, which introduces undesired oscillations to the network [22,21,25].…”
Section: Introductionmentioning
confidence: 99%
“…The topographic pattern of connection is interrupted in the network edges, changing the activity in the network boundary [14,15]. A classic solution adopted to this problem is the torus connection, which introduces undesired oscillations to the network [22,21,25].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of multiple traveling waves can form complex spatiotemporal patterns [4,47]. It has been shown, in spiking neural networks [46,[48][49][50][51]that transmission delays [41], the spatial reach of connections [7] and the strength of inhibition of the excitatory-inhibitory networks influence the emergence of spatiotemporal patterns, such as asynchronous and irregular activity, or propagating waves. Most previous modeling studies have shown that the formation of spatiotemporal patterns such as traveling waves in neural networks has mainly been investigated by means of phenomenological neural-field models.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this work is to analytically and numerically study the static and dynamic bifurcations and spatio-temporal wave patterns generated by the classical neural field model with an exponential temporal kernel. This form of the temporal kernel is more general than the Green's function used in [16] and [20]. In [20] the temporal connectivity kernel is the product of an alpha function and the Heaviside function, which yields a function with the same properties as the Green's function, and thus yields the same characteristic polynomial as in [16].…”
Section: Introductionmentioning
confidence: 99%
“…This form of the temporal kernel is more general than the Green's function used in [16] and [20]. In [20] the temporal connectivity kernel is the product of an alpha function and the Heaviside function, which yields a function with the same properties as the Green's function, and thus yields the same characteristic polynomial as in [16]. We recall that the Green's function G(t, t ) is the solution to LG(t, t ) = δ(t−t ) satisfying the given boundary conditions, where L is a differential operator.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation